2022
DOI: 10.3390/ijms231810559
|View full text |Cite
|
Sign up to set email alerts
|

HMG20A Inhibit Adipogenesis by Transcriptional and Epigenetic Regulation of MEF2C Expression

Abstract: Obesity and its associated metabolic disease do serious harm to human health. The transcriptional cascade network with transcription factors as the core is the focus of current research on adipogenesis and its mechanism. Previous studies have found that HMG domain protein 20A (HMG20A) is highly expressed in the early stage of adipogenic differentiation of porcine intramuscular fat (IMF), which may be involved in regulating adipogenesis. In this study, HMG20A was found to play a key negative regulatory role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This regulatory interplay may hold significant implications in the context of adipogenic differentiation. 20 Our study identified a homologous circRNA of MEF2C in porcine intramuscular preadipocytes through a series of experimental procedures. This circRNA originates from exons 2 and 3 of the MEF2C gene, and in line with established nomenclature principles for circRNAs, we designated it as circMEF2C(2, 3).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This regulatory interplay may hold significant implications in the context of adipogenic differentiation. 20 Our study identified a homologous circRNA of MEF2C in porcine intramuscular preadipocytes through a series of experimental procedures. This circRNA originates from exons 2 and 3 of the MEF2C gene, and in line with established nomenclature principles for circRNAs, we designated it as circMEF2C(2, 3).…”
Section: Discussionmentioning
confidence: 96%
“…Our findings also indicate that MEF2C operates as a downstream target gene of HMG20A and experiences co-regulation by HMG20A and LSD1 , implicating its involvement in adipose generation. 20 Nonetheless, the upstream regulatory mechanisms governing MEF2C remain unexplored. RNA sequencing was performed the expression of circMEF2C(2, 3) decreased in obese-type pig breeds (Mashen) compared with lean-type pig breeds (Large White).…”
Section: Introductionmentioning
confidence: 99%
“…HMG20A silencing promoted adipogenic differentiation of porcine myogenic stromal vascular fraction (SVF) cells and C3H10T1/2 cells and thus it negatively regulates adipogenesis, hence not likely to promote diabetes. 52 Yet, the pathophysiological consequence of the rs7178572 SNP associated with adipogenesis is still unknown. The SNP rs758747 (C>T) located in NLR family CARD domain containing 3 ( NLRC3 ) gene was also found to be negatively associated with restenosis in diabetic women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al. found that HMG20A exerts inhibitory effects on adipogenesis in porcine muscle SVFs and C3H10T1/2 cells through its interaction with lysine-specific demethylase 1 (LSD1) ( 64 ). Mozzetta et al.…”
Section: Regulatory Mechanisms Of Intermuscular Adipogenesismentioning
confidence: 99%
“…In addition, Li et al found that HMG20A exerts inhibitory effects on adipogenesis in porcine muscle SVFs and C3H10T1/2 cells through its interaction with lysine-specific demethylase 1 (LSD1) (64). Mozzetta et al found that histone deacetylase inhibitors (HDACis) repressed the adipogenic potential of FAPs and enhanced the myogenic differentiation of SCs in young dystrophic mice but not in old mdx mice (65).…”
Section: Key Signaling Moleculesmentioning
confidence: 99%